2022
DOI: 10.1590/fst.06321
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic effect of porang oligo-glucomannan using fecal batch culture fermentation

Abstract: Porang glucomannan is a polysaccharide extracted from Amorphophallus oncophylus and its degradation product is porang oligoglucomannan (POG). It contains glucomannan, which has been used as an emulsifier, thickener, or as a nutritional supplement to counter many diseases. While it is believed to have health benefits, there are only limited studies exploring this aspect of porang glucomannnan (PGM). It was hydrolyzed using β-mannanase to obtain POG under optimal conditions: reaction temperature of 37 °C, reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…8 Porang glucomannan also has a prebiotic effect. 17 Another research revealed that supplementation with inulin, another prebiotic substance, improved glucose levels, serum insulin, and HOMA-IR (Homeostatic Model Assessment of Insulin Resistance) in rats model of metabolic syndrome. 18 GLUT-4, an insulin transporter found in adipose tissue and muscle, predicts metabolic syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…8 Porang glucomannan also has a prebiotic effect. 17 Another research revealed that supplementation with inulin, another prebiotic substance, improved glucose levels, serum insulin, and HOMA-IR (Homeostatic Model Assessment of Insulin Resistance) in rats model of metabolic syndrome. 18 GLUT-4, an insulin transporter found in adipose tissue and muscle, predicts metabolic syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…The pH affects product growth and yield in microbial deep fermentation (Anggela et al, 2022;Kumar et al, 2010). Since the acidity of the fermentation broth was constantly changing during the fermentation process, the method of automatic feeding was adopted in this experiment, and sodium hydroxide and hydrochloric acid were selected to control the pH to maintain a fixed value.…”
Section: Optimization Of Fermentation Condition In Bioreactormentioning
confidence: 99%